Establishment of patient‐derived organotypic tumor spheroid models for tumor microenvironment modeling. (9th July 2021) - Hong, Hye Kyung; Yun, Nak Hyeon; Jeong, Ye‐Lin; Park, Jeehun; Doh, Junsang; Lee, Woo Yong; Cho, Yong Beom
Abstract: Patient‐derived cancer models that reconstitute the characteristics of the tumor microenvironment may facilitate efforts in precision immune‐oncology and the discovery of effective anticancer therapies. Organoids that have recently emerged as robust preclinical models typically contain tumor epithelial cells and lack the native tumor immune microenvironment. A patient‐derived organotypic tumor spheroid (PDOTS) is a novel and innovative ex vivo system that retains key features of the native tumor immune microenvironment. Here, we established and characterized a series of colorectal cancer PDOTS models for use as a preclinical platform for testing effective immunotherapy and its combinations with other drugs. Partially dissociated (> 100 μm in diameter) tumor tissues were embedded in Matrigel‐containing organoid media and subsequently formed into organoid structures within 3 to 7 days of culture. The success rate of growing PDOTS from fresh tissues was 86%. Morphological analysis showed that the PDOTSs varied in size and structure. Immunofluorescence and flow cytometry analysis revealed that the PDOTSs retained autologous tumor‐infiltrating lymphoid cells and tumor‐infiltrating lymphoid cells were continually decreased through serial passages. Notably, PDOTSs from tumors from a high‐level microsatellite instability‐harboring patient were sensitive to anti‐PD‐1 or anti‐PD‐L1 antibodies. Our results demonstrate that the PDOTS model in which the tumor immune microenvironment is preserved may represent an advantageous ex vivo system to develop effective immune therapeutics. Abstract : As stated in the manuscript, we established and characterized a series of colorectal cancer PDOTS models for use as a preclinical platform for testing effective immunotherapy and its combinations with other drugs. PDOTSs from tumors from a high‐level microsatellite instability‐harboring patient were sensitive to anti‐PD‐1 or anti‐PD‐L1 antibodies. Our results demonstrate that the PDOTS model in which the tumor immune microenvironment is preserved may represent an advantageous ex vivo system to develop effective immune therapeutics.